The Golden Age of the Quantity Theory. - Laidler, David E. W. (Princeton University Press, 2014)
How did neoclassical monetary economics, as epitomized by the work of Fisher, Wicksell, and the Cambridge School, evolve from the classical orthodoxy that dominated economics in the 1870s? To answer this question, David Laidler considers the interaction of theoretical developments with contemporary policy debates about bimetallism and the evolution of the gold exchange standard. He argues that neoclassical monetary economics, in which the quantity theory of money played a central role, laid the intellectual groundwork for the replacement of the gold standard by various managed monetary syst.
Subject Index.
Keywords: Quantity theory of money.; Neoclassical school of economics.; Théorie quantitative de la monnaie.; École néoclassique d'économie politique.; BUSINESS & ECONOMICS -- Money & Monetary Policy.; BUSINESS & ECONOMICS -- Finance.; Neoclassical school of economics; Quantity theory of money